Closed circuit television - Cieszynski, Joe (Elsevier/Newnes, 2007)
Closed Circuit Television (CCTV) surveillance remains a growing industry in response to increased security threats, and whilst new developments have brought clearer images, digital recording and high speed data transmission, effective security systems still rely upon proper specification and installation by engineers with an in depth knowledge of CCTV principles and technology. The third edition of Closed Circuit Television provides a thorough technical guide for all those involved in the design, specification, installation and maintenance of CCTV systems. Fully dual-standard for PAL an.